PROFIL ORGANISASI PERSAUDARAAN SETIA HATI TERATE (PSHT) DI KOTA PEKANBARU - Putri Dewi Lase; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study, entitled "Profile of the organization Persaudaraan Setia Hati Terate (PSHT) In the city of Pekanbaru". The research was conducted in the city of Pekanbaru, with the aim to determine how the profile and role of the organization Persaudaraan Setia Hati Terate (PSHT) In the city of Pekanbaru. The method used in this study Qualitative research methods Descriptive namely, that the discussion of this study are presented and analyzed in the form of words of description (description) with a qualitative approach. In addition, this study also was supported by the implementation of in-depth interviews to sources (informants) as determined by the researchers first. From the results of these interviews, the obtained descriptions are very supportive to the validity of the data that are the focus of research. Based on the results of the research, that the profile of the organization Persaudaraan Setia Hati Terate (PSHT) Pekanbaru Branch includes several things such as: At the beginning of establishment of PSHT Branch of Pekanbaru, figures PSHT Founder Branch of Pekanbaru, Stewardship Branch PSHT Pekanbaru, Javanese proverb meaning the Persaudaraan Setia Hati Terate (PSHT). As for the role played by the Persaudaraan Setia Hati Terate (PSHT) Branch Pekanbaru is His role in the field of sports, in society, and also a role in preserving the culture of martial arts that (pencak silat) SH Terate. Keywords: Profile, Organization, Branch PSHT Pekanbaru